THE EFFECTIVENESS OF MINDLY IN TEACHING READING COMPREHENSION - Gina Larasaty; Putri Fitriyani (Universitas Sarjanawiyata Tamansiswa, 2022)
Coronavirus has forced schools to teach online, where learning uses a variety of applications, one of which is Mindly. Therefore, the writer is interested in conducting research to find out the effectiveness of Mindly in teaching reading comprehension. Grounded in quasi-experiment method with the design pre-test and post-test, this research is conducted on the 26 students from 2 class at SMPN 1 LOHBENER. The result of the pre-test students score in control class showed that the average was 42,77 and the pre-test students score in experiment class showed the average was 47,08. The post-test total scores in control class showed the average was 60,62. And the result of post-test the total scores in experiment class showed the average was 59,08. Then, the statistical analysis showed that the value tobs was 0,9999 while the value of ttable 0,6 which means that the value of tob higher than ttable 0,9999 > 0,6 (tobs > ttable). From the result of statistical analysis, it can be concluded that tobs was higher than ttable (tobs > ttable) it means that Alternative Hypothesis (Ha) was accepted while Null Hypothesis (Ho) was rejected. It means that using Mindly does not give positive effect to students’ reading comprehension